THE EFFECT OF LOCATION, PRICE, AND WORK SERVICES ON CONSUMER SATISFACTION AT PT RUDANG HOTEL BERASTAGI - Jese Tingkos Tampubolon; Ricky Rafii Ritonga; Herlina Pasaribu; Eki Ro Putra Br Limbong (Institute of Computer Science (IOCS), 2022)
The research location was conducted at PT Rudang Hotel Berastagi, a company engaged in hotel accommodation services. At the time the research was conducted the company experienced a decrease in consumer satisfaction as indicated by a decrease in visitors. The phenomenon of location problems regarding the number of accommodations that offer similar services so that the choice of consumers in choosing is increasing. Regarding the price, consumers complain that the price does not match the facilities such as a delux room but the facilities are the same as the standard room price. Problems in service work, less friendly receptionist in serving consumers. Theoretical limitations will be limited through the management of marketing locations, prices, job services, and customer satisfaction. This study uses simple random sampling with the Slovin formula. With a population of 2304 consumers and 30 people for validity testing and a sample of 100 consumers. Quantitative research was chosen as the research method.The analysis used in the form of multiple analysis methods, determination testing and simultaneous testing of F count (5.891) > F table (3.09) and partial testing of location (0.662 < 1.984), price (3.599 > 1.984), and job services (2.731 > 1.984 ). The results showed that location had no effect on customer satisfaction, but price and work service showed a positive and significant effect on customer satisfaction with a ratio of 12.9%.